2016
DOI: 10.1007/s10964-016-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knowledge: Examining Reporter Discrepancies and Links to School Engagement Among Middle School Studies

Abstract: It is well established that parental knowledge contributes to adolescents' well-being and school success and scholars have noted that parents and adolescents report different levels of knowledge. Discrepancies in parental knowledge have implications for adolescent outcomes such as risk behaviors, but little is known about the implications of knowledge discrepancies for adolescents' school outcomes. The present study examined discrepancies in parent and adolescent reports of parental knowledge and investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Adolescent-reported parental knowledge has been demonstrated to support adolescents' psychological well-being and school adjustment (Dotterer and Wehrspann 2016;Hamza and Willoughby 2011;Stattin and Kerr 2000). The research has also shown the relationship between parental knowledge and externalizing behaviors among immigrant adolescents (Cristini et al 2015;Walsh et al 2014;Wang et al 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Adolescent-reported parental knowledge has been demonstrated to support adolescents' psychological well-being and school adjustment (Dotterer and Wehrspann 2016;Hamza and Willoughby 2011;Stattin and Kerr 2000). The research has also shown the relationship between parental knowledge and externalizing behaviors among immigrant adolescents (Cristini et al 2015;Walsh et al 2014;Wang et al 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Second, this study principally relied on self-report measures and adolescent respondents. Although previous research has indicated that adolescents can provide valuable and accurate information regarding interparental conflict, parental knowledge, and delinquency (Dotterer and Wehrspann, 2016;Fan et al, 2018), caution should be exercised regarding the possible impacts of shared method variance and social desirability on the data. Further research should utilize additional respondents (e.g., multiple informants, including peers, teachers, and parents), which may capture more credible information and reduce the shared method variance.…”
Section: Discussionmentioning
confidence: 99%
“…The child-parent communication indicator included data on how often the children discussed their school day with their parents, how often children agreed with parents what time they would come home when they went out, how often the children’s parents talked with their friends when they meet them and how often the children’s parents supported and encouraged them. Previous studies have also indicated that discussing schoolwork with parents [ 7 , 13 ], family rules and boundaries [ 8 , 16 ] and supervision by parents [ 7 , 40 , 41 , 42 , 43 , 44 ] were factors that had a positive impact on the child’s school engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Good quality child-parent relationships have been associated with higher levels of school engagement by boys and girls in primary school, junior high school and high school [ 28 , 29 , 30 , 31 ]. High parental monitoring has been shown to have a positive impact on school engagement, which can be measured by asking questions such as whether a parent knows who their child spends their free time with [ 7 , 40 , 41 , 42 , 43 , 44 ]. Positive associations between parental monitoring and school engagement have been reported for both genders [ 45 ] and in single and two-parent families [ 46 ].…”
Section: Introductionmentioning
confidence: 99%